Development of a digital mental health intervention for youth with ADHD: exploring youth perspectives on wants, needs, and barriers - Storetvedt, Maren Helene Rinke; Kahlon, Smiti; Berg, Karin; Sundfjord, Ingeborg Alvheim; Nordgreen, Tine (Frontiers in Digital Health, 2024)
BackgroundAttention deficit hyperactivity disorder (ADHD) is a mental health disorder affecting five to eight percent of children and youth worldwide. Inattention, impulsivity, and hyperactivity are core symptoms, which often leads to comorbid disorders and impairments. Increased prevalence of ADHD among youth requires development of accessible and scalable interventions. Digital interventions for ADHD show promising results for adults, yet insight into youths perspectives and needs from digital ADHD interventions is lacking. This study is set in a person-based approach and explore what youths want and need from a therapist-guided digital intervention for ADHD.MethodsExploratory individual interviews were conducted with youths aged 13–16 years diagnosed with ADHD (N = 16). Participants with an ADHD diagnosis were recruited primarily via social media. The interview guide was based on research, treatment guidelines, and clinical expertise. The study applied reflexive thematic analysis, within a Big Q framework. Codes and themes were generated in Nvivo.ResultsFour main themes and sub-themes were generated: (1) Tailoring the intervention to youths with ADHD (Push the right buttons; Stumbling blocks), (2) Managing ADHD (Planning and Focus; Regulation and Balance; Social interactions), (3) Me and my ADHD (Insight and Understanding; Accept and Normalization), and (4) Balance between support and independence.DiscussionThe findings suggest that youths with ADHD prefer stimulating and interactive treatment and are aversive to overwhelming, passive content. The intervention and therapist should encourage empowerment by supporting the youths autonomy in managing their ADHD. Future research is needed to investigate feasibility for person-based approaches to digital mental health treatments. Furthermore, parent perspectives on digital treatment for youths with ADHD should be investigated.